Analyzing Customer Satisfaction on Arthaspa Services with the C4.5 Algorithm Approach - Sofian Wira Hadi; Wawan Kurniawan; Kudiantoro Widianto; Ibnu Alfarobi (Kresnamedia Publisher, 2020)
Customer or buyer satisfaction is closely related to how a seller of services or a store serves its visitors. Good service for visitors also makes a good impression on visitors, while the opposite will cause a very bad or unfavourable impression in the eyes of customers, and may also lead to the reluctance of visitors to come back and lose the seller's opportunity to get potential buyers to become customers. This study attempts to analyze customer satisfaction with the services provided by Arthaspa outlets in Grand Kemang hotels using the C4.5 Algorithm approach. The attributes used are comfort, cleanliness, tidiness, and price. samples taken are customers who have transacted at least once.